2022
DOI: 10.1108/ijoem-06-2021-0859
|View full text |Cite
|
Sign up to set email alerts
|

Work environment, HR practices and millennial employee retention in hospitality and tourism in Bangladesh

Abstract: PurposeThis study examines the relationship between HR practices and millennial employee retention in the tourism industry in Bangladesh. It investigates the moderating role of the work environment in the relationship between HR practices and employee retention in the industry.Design/methodology/approachThe researchers used non-probability judgemental sampling to collect 384 questionnaires through a survey of millennial employees. Partial least square-based structural equation model (PLS-SEM) was used to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 84 publications
1
10
1
Order By: Relevance
“…, 2018). However, H1b contradicts earlier studies that proposed that employees with better compensation and performance appraisal stay longer with their employer (Cherif, 2020; Islam et al. , 2022; Ngoma and Ntale, 2019).…”
Section: Discussioncontrasting
confidence: 70%
“…, 2018). However, H1b contradicts earlier studies that proposed that employees with better compensation and performance appraisal stay longer with their employer (Cherif, 2020; Islam et al. , 2022; Ngoma and Ntale, 2019).…”
Section: Discussioncontrasting
confidence: 70%
“…Employee retention is defined as an organization's ability to prevent proficient employees from withdrawing from the organization (Tyagi, 2021). According to Islam et al (2022), employee retention is a voluntary move by an organization to create an environment that engages employees in the long term. Retention is, therefore, viewed as a logical inverse of turnover, as it indicates the behavior of continue/stay rather than quitting or leaving the organization (Fahim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the best out of retention practices, Buers, Karpinska, and Schippers (2018) argued that managers evaluate various pieces of information and subsequently take a retention decision that they believe will maximize the benefits for the organization. In a study conducted by Islam et al (2022), the researchers argued that employee retention could be reduced significantly if the organization successfully ensures proper human resource practices. They indicated that employees would be willing to stay if they trusted that the organization would not deprive their cogent training and compensation, allow them to participate in important decision-making, and ensure a safe and secure work environment.…”
Section: Introductionmentioning
confidence: 99%
“…According to Herzberg theory, achievement of higher order needs such as career development leads to JS, whereas its absence leads to no satisfaction. Millennial employees seek discretion and freedom to work efficiently (Islam et al, 2022). So, incorporating EE increases employees' capabilities to perform that triggers OCD (Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%